Rehabilitation of mangrove forests project, Southern Mekong Delta, Vietnam (Ca Mau, 1999)
The main aim of the project was to rehabilitate the degraded belt of magrove forests through planting of protection-and production forest, with community participation, and to enhance forest protection.
Keywords: Mangrove plants,Cây đước